Meeting Immigrant Community College Students’ Needs on One Greater Toronto Area College Campus - Kilbride, Kenise Murphy; D’Arcangelo, Lucy (Canadian Journal of Higher Education, 2002)
One hundred and forty-six students who entered Canada after their twelfth birthday and are now in one of six technical programs on a Greater Toronto Area (GTA) community college campus were surveyed. Technical programs enrol over half the students on this campus, and the six programs enrol over half the technical students. Over half had entered Canada past the usual age for high school (and over two-thirds in the past six years), making the college their point of entry into the Canadian educational system. Degrees and types of needs were analyzed, as well as degrees and sources of support. Differences occurred across numerous background traits but the most striking finding is the students’ perception of a low degree of support from the college itself. This has clear policy implications for funders of GTA colleges, which attract such high numbers of new immigrants to Canada.